USE OF OPS CONCRETE IN SEMI-PRECAST CONCRETE SLAB - Kurian, V.J.; Doh, S.I.; Ideris, Z.; Narayanan, S.P; Gungat, L. (World Engineering Congress, 2007)
Malaysia produces more than half of the world’s output of palm oil, planted over 4.05 million hectares of land, yielding about 18.88 tonnes per hectare of fresh fruit branches (FFB). The palm oil extraction produces large quantities of waste namely fibre, shell and effluent which are usually disposed by incineration or left to rot. This pollutes the environment and is harmful to the ecosystem. The results reported here are from a research project funded by the Construction Industry Development Board (CIDB) Malaysia, that aims to utilise processed Oil Palm Shell (OPS) as aggregate in making OPS concrete semi-precast flooring slabs. Utilising OPS in concrete saves the problem of disposing the solid waste while conserving the natural aggregates that would have been used otherwise. Sandstone was used as coarse aggregate for the bottom layer of concrete in the semi-precast slab. Coarse aggregates such as granite, sandstone and OPS were used for the cast-in-situ top layer of concrete. The thickness of bottom and top layers were 50mm and 75mm respectively. A total of six slabs with different toppings were cast and tested. Data presented include the characteristics of deflection and cracking behavior. The results showed that the semi-precast slab with topping of OPS concrete deflected maximum (94 mm) compared to similar slabs with toppings of granite concrete (70 mm) and sandstone concrete (71 mm). The investigation also revealed that the type of topping did not affect the strength of the slab significantly. The flexural behavior of all the three types of semi-precast slabs complied with the requirements specified by the current Codes of Practice. Semi-Precast slab with the topping of OPS concrete has an added advantage that it is lightweight, thereby reducing the cost of construction.